Implementation Of Blended Learning During Covid-19 Pandemic On Learning Interests And Outcomes - Hikmah, Zulhani Karunia; Purwati, Nining; Mukminah, Mukminah (Biota, 2022)
This research aims to determine the effect of blended learning on students’ learning interests and outcomes in musculoskeletal system subjects. The research benefit proved that blended learning could be a practical alternative learning approach during the pandemic. This research was carried out in October 2021. The research design was experimental and used a quantitative approach through pre-tests and post-tests. Sampling data collection employed cluster random sampling technique. The research sample consisted of 21 students from the experimental group and 21 students from the control class. The control class was given a full online learning treatment, and the experimental class was given a blended learning treatment. A hypothesis testing data analysis was performed using the ANCOVA test. Then, online learning was conducted over four meetings and offline learning was conducted in one meeting. The average learning interest in the experimental class was 124.3, and the control class was 117.62, which was categorized as sufficient. The average percentage increase in learning outcome scores in the experimental class was 70.57%, while it was only 60.48% in the control class. Data processing outcomes on learning interest obtained a value of 0.009 with α = 0.05. Meanwhile, values processed on learning outcomes obtained a value of 0.02 with α = 0.05. The increase in students’ interest and learning outcomes was caused by varied learning styles using the blended learning approach. Hence, based on these data, blended learning significantly affected students’ learning interests and outcomes.